ACİL SERVİSTE HEMORAJİK İNMELİ HASTALARDA KREATİN KİNAZ-MB, TROPONİN I, D-DİMER DEĞERLERİNİN GLASKOW KOMA SKORU VE MORTALİTE İLE İLŞKİSİ - BAŞTÜRK, MUSTAFA (Fırat Üniveristesi, 2007)
İnme, kalp hastalıkları ve kanserden sonra ölümün 3. nedeni olup sekelbırakıcı bir hastalıktır. Hemorajik inmeler, iskemik tipten az görülmesine karşın, dahaölümcül seyretmektedir. D-Dimer (DD) ve kardiak markerlar inmelerdeartabilmektedir.Ekim 2006-Ocak 2007 tarihleri arasında acil servisde hemorajik inme tanısıkonulan hastalar çalışmaya alındı. Bu hastalardan 0. ve 3. gün kanda D-Dimer,kreatin kinaz-mb (CK-MB), Troponin-I (Tn-I) çalışılarak, Glaskow Koma Skoru(GKS) ve mortalite ile ilişkisi incelendi.Çalışmaya 28'i erkek, 23'ü kadın 51 hasta alındı. Hastaların %72,6'sındahipertansiyon mevcuttu. Kırkbeşinde intraserebral, 6'sında subaraknoid kanama tesbitedildi. Yirmibir hasta eksitus oldu. Taburcu olanlarla ölen hastaların bulunan DD,CK-MB, Tn-I, GKS değerleri karşılaştırıldı. D-Dimer ölen grupta 3062Â±1781 ng/ml,taburcu grupta 766Â±153 ng/ml olup, karşılaştırıldığında istatiksel anlamlılık mevcuttu(p<0.05). CK-MB ve Troponin-I karşılaştırıldığında mortalite açısından istatikselfarklılık yoktu (p>0,05). GKS ölen grupta 7,2Â±3,8 taburcu olan grupta 13,7Â±1,63olup, istatiksel anlamlılık mevcuttu (p<0,05). D-Dimer ile GKS mortalite açısındankarşılaştırıldığında, aralarında negatif korelasyon mevcuttu. Ölen grupla taburcu grupkarşılaştırıldığında, kan glukoz, beyaz küre, Na, myoglobin değerlerinin artmasının,beyin tomografisinde intraserebral kanamalı hastalarda ventriküle açılımın, şiftetkisinin ve lezyon çapının artmış olmasının mortaliteyi arttırdığını belirledik.Hemorajik inmeli hastalarda, genel durumun bozulmasına paralel olarak DDarttığını ve artmış DD düzeyi ile birlikte, GKS'nin düşük olmasının mortalite ileilişkili olabileceğini belirledik. Bu konuda daha fazla çalışmaya ihtiyaç olduğunudüşünmekteyiz.Anahtar Kelimeler: Hemorajik inme, GKS, DD, mortalite.1

The relationship between CK-MB, Tn-I, D-Dimer with GCS andmortality in patients presented to Emergency Department with hemorrhagestrokeStroke is a common disorder that remains the third leading cause of death inwestern countries and a major cause of disability in the elderly. Althoughhemorrhagic strokes are seen less than ischemic type, is more fatal than ischemicstroke. D-Dimer (DD) and cardiac markers may increase in stroke.The patients who were diagnosed with hemorrhagic stroke in emergeneyservice between October 2006-January 2007 were taken into the study. İn the firstregistration of these patients and on the third day, DD, creatin kinaz-MB (CK-MB),Troponim-I (Tn-I) were determined and the relation between Glasgow Coma Scalaand mortality was evaluated.51 patients were taken into the study, 28 men, 23 women. 72.6%of thepatients had hypertension. İn these patients, 6 patients have subaracnoid hemorrhageand 45 have intracerebral hemorrhage. 21 patients were died. DD, CK-MB, Tn-I andGCS values were compaired between the patients who died and the ones discharged.D-Dimer values were 3662+1781 ng/ml in the ex-group and 766+153 ng/ml in thedischarged group, and when compared, it was statistically significant (P<0,05). whenCK-MB and Tropin I were compared, there was not a statisticaly difference inmortality. GCS was statistically significant (P<0,005) in the ex-group, When DD andGCS were compared in the view of mortality, there was a negative corralition amongthem. When the ex-group and the discharrged group were compared, we found thatthe values of blood glucose, white blood cell, Na, myoglobin, ventricule?s deviationin the brain computerize tomography of the patients with intracerebral hemorrhage,the effect of shift and the increased dimension of the lession İncreased the mortality.We determined that, in the patients with hemorrhagic stroke, DD levelsincreased in paralel with the deterioration of the general situation and togetter withthe increased DD level, the low GCS, could be related to the mortality. We believethat further studies are needed to this subject.Key Words: Hemorrhagic stroke, Glasgow Coma Scala, D-Dimer, Mortality.2
The relationship between CK-MB,Tn-I,D-Dimer with GCS and mortality in patients to Emergency Deparment with hemorrhage stroke
Keywords: İlk ve Acil Yardım